LEITURA: CONSTITUIÇÃO DO PROFESSOR - Reghelin, Thais; Souza, Andressa De; Schmidt, Andressa; Klering, Luana Paula; Kieslich, Jací (Salão do Conhecimento, 2017)
Projeto de pesquisa realizado no curso de Pedagogia da Unijuí.